2016
DOI: 10.1111/radm.12243
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dimensions of power influencing knowledge integration in supply chains

Abstract: This study investigates how multiple dimensions of power each facilitate knowledge integration within innovation projects in supply chains and their interrelationships. Adopting a process perspective of knowledge, we offer an alternative to much of the existing debate, which has focussed on the possession of resources. We collected data from four case‐study Original Equipment Manufacturers and six associated suppliers and analysed these using Template Analysis and cross‐case analysis. Our findings reveal how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Different tactics might be deployed simultaneously on various properties of the same technology. Hence, Matheus et al (2017) demonstrated that it is the cumulative effects of those three dimensions of power that explain knowledge integration in innovation and the ability to overcome conflicts. Furthermore, Kraus and Strömsten (2016) highlighted that combination of power determines the ability of organizations to collaborate in the electronics industry.…”
Section: The Effects Of Influence Tactics On Path Constitutionmentioning
confidence: 99%
“…Different tactics might be deployed simultaneously on various properties of the same technology. Hence, Matheus et al (2017) demonstrated that it is the cumulative effects of those three dimensions of power that explain knowledge integration in innovation and the ability to overcome conflicts. Furthermore, Kraus and Strömsten (2016) highlighted that combination of power determines the ability of organizations to collaborate in the electronics industry.…”
Section: The Effects Of Influence Tactics On Path Constitutionmentioning
confidence: 99%
“…Change requests have a different meaning to different companies and scholars (e.g. Matheus et al , 2016; Pattit and Wilemon, 2005; Tang, 2015). In the project studied in this paper, the terms and processes were interpreted, primarily, as changes to technical requirements, and subsequent changes to project scope and scheduling.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As an industrializing country, China faces the decisions of ‘Make’ or ‘Buy’, or somewhere in between (White, ). The following strategies are defined to describe the situation (Chan et al, ): (1)Indigenous Innovation (Lazonick, ; Yang and Shu, ; Li‐Ying et al, ; Li and Yu, ). (2)Imitative Innovation (Mukoyama, ; Yang and Shu, ; Cheng and Shiu, ; Li‐Ying et al, ). (3)Collaborative Innovation (Yang and Shu, ; Wang and Li, ; Velamuri et al, ; Chen et al, ; Dooley et al, ; Matheus et al, ). International Technology Transfer (Farhang, ; Guan et al, ; Salicrup and Fedorkova, ; Bin, ; Li‐Ying et al, ). …”
Section: Case Applicationmentioning
confidence: 99%
“…(2) Imitative Innovation (Mukoyama, 2003;Yang and Shu, 2005;Cheng and Shiu, 2008;Li-Ying et al, 2014). (3) Collaborative Innovation (Yang and Shu, 2005;Wang and Li, 2007;Velamuri et al, 2015;Chen et al, 2016;Dooley et al, 2016;Matheus et al, 2016). International Technology Transfer (Farhang, 1997;Guan et al, 2006;Salicrup and Fedorkova, 2006;Bin, 2008;Li-Ying et al, 2014).…”
Section: Strategy Sub-criteriamentioning
confidence: 99%